Effect of orange sweet potato (ipomoea batatas) flour substitution on the pasting, rheological and textural properties of fish-flours mixtures of extruded fish crackers / Noorakmar Abd Wahab - Abd Wahab, Noorakmar (Institute of Graduate Studies, UiTM, 2012)
Fish cracker or more commonly known as keropok in Malaysia is popular snack food among countries in the ASEAN region. The main starchy flour component used is tapioca starch (Manihot esculenta) that gives cracker expansion which was strongly correlated with consumer preference. Very few studies have been carried out on potential of other tuber sources to replace tapioca flour in formulation of fish crackers. Besides, the information on utilization of freshwater fish in fish crackers was also limited. This study highlighted the potential usage of orange sweet potato (Ipomoea batatas) flour as ingredient to substitute tapioca flour in fish cracker and as for types of fish, the red tilapia (Oreochromis niloticus) is used. Fish cracker manufacturing is mostly practised in small scale and extrusion cooking could simplify the process of stuffing and steaming.